Investigating swearing motives among student-athletes during attending sports training program and competitions - Setyawati, Heny; Sumekto, Didik Rinan; Rahayu, Tandiyo (LPMPP Universitas Negeri Yogyakarta, 2022)
This study aims at investigating student-athletes’ swearing motives when attending sports training program and competitions. This study involved 210 respondents (n = 201, Mage = 21.65; SD = 3.994), which were organized by the National Sports Committee of Indonesia, Jawa Tengah Province, Indonesia. Data collection used a self-rated questionnaire with a 5-Likert scale measuring for expressing anger, stressing from opponents, relieving tension and frustration, and customizing daily expression using the IBM SPSS software analyses. The results postulated that the scaled determinants empirically triggered student-athletes’ swearing motives in expressing anger (M = 2.13; SD =.922), stressing from opponents (M = 2.15; SD = 1.005), relieving tension and frustration (M = 1.98; SD = 1.019), and customizing daily expression (M = 2.10; SD = 1.087), although there were no statistically significant differences among those determinants. The dependent variable showed that F (4, 202), p = .000; Wilks’ Lambda = .58; and partial eta squared = .13, whilst the normality, linearity, and homoscedasticity consequences were not transgressive. Hence, among the determinants had positive correlations (r = .769, n = 210, p.01), where student-athletes’ swearing expression levels sequentially placed stressing from the opponents associated with expressing anger, customizing daily expression, and relieving tension and frustration. Meanwhile, social media was mostly eligible to determine gender-based swearing expressions (females = 50.4%, males = 43.2%), expressed by the local swearwords. These swearing motives constitute student-athletes’ intrinsic and extrinsic relationships, whether positive or negative actions that conditionally differentiate student-athletes’ psychological well-being across the dimensions of self-acceptance, autonomy, environment and personal maturation